Answer: x = 16
Step-by-step explanation:
Solve for x by simplifying both sides of the equation, then isolating the variable. :)
Answer: ![\cos^{-1} \left(\frac{-37}{\sqrt{7298}} \right) \approx 115.665^{\circ}](https://tex.z-dn.net/?f=%5Ccos%5E%7B-1%7D%20%5Cleft%28%5Cfrac%7B-37%7D%7B%5Csqrt%7B7298%7D%7D%20%5Cright%29%20%5Capprox%20115.665%5E%7B%5Ccirc%7D)
Step-by-step explanation:
![u \cdot v=(1)(8)+(-9)(5)=-37\\\\|u|=\sqrt{1^{2}+(-9)^{2}}=\sqrt{82}\\\\|v|=\sqrt{8^{2}+5^{2}}=\sqrt{89}\\\\\cos \theta=\frac{-37}{\sqrt{82}\sqrt{89}}\\\\\theta=\cos^{-1} \left(\frac{-37}{\sqrt{82}\sqrt{89}} \right)\\\\\theta=\boxed{\cos^{-1} \left(\frac{-37}{\sqrt{7298}} \right) \approx 115.665^{\circ}}](https://tex.z-dn.net/?f=u%20%5Ccdot%20v%3D%281%29%288%29%2B%28-9%29%285%29%3D-37%5C%5C%5C%5C%7Cu%7C%3D%5Csqrt%7B1%5E%7B2%7D%2B%28-9%29%5E%7B2%7D%7D%3D%5Csqrt%7B82%7D%5C%5C%5C%5C%7Cv%7C%3D%5Csqrt%7B8%5E%7B2%7D%2B5%5E%7B2%7D%7D%3D%5Csqrt%7B89%7D%5C%5C%5C%5C%5Ccos%20%5Ctheta%3D%5Cfrac%7B-37%7D%7B%5Csqrt%7B82%7D%5Csqrt%7B89%7D%7D%5C%5C%5C%5C%5Ctheta%3D%5Ccos%5E%7B-1%7D%20%5Cleft%28%5Cfrac%7B-37%7D%7B%5Csqrt%7B82%7D%5Csqrt%7B89%7D%7D%20%5Cright%29%5C%5C%5C%5C%5Ctheta%3D%5Cboxed%7B%5Ccos%5E%7B-1%7D%20%5Cleft%28%5Cfrac%7B-37%7D%7B%5Csqrt%7B7298%7D%7D%20%5Cright%29%20%5Capprox%20115.665%5E%7B%5Ccirc%7D%7D)
Answer:
Assuming x as the length of the longest side, x is 16 units.
Step-by-step explanation:
![x+(x-2)+(x-4)=42\\3x-6=42\\3(x-2)=42\\x-2=14\\x=16](https://tex.z-dn.net/?f=x%2B%28x-2%29%2B%28x-4%29%3D42%5C%5C3x-6%3D42%5C%5C3%28x-2%29%3D42%5C%5Cx-2%3D14%5C%5Cx%3D16)
Step-by-step explanation:
as the denominator (x+3) is in both you need only one denominator to be multiplied in first rational number .
<u>2</u><u>x</u><u> </u><u>(</u><u>x-2</u><u>)</u><u>. </u><u> </u><u> </u>+ <u>5</u><u>. </u><u> </u><u> </u><u> </u><u> </u><u> </u>
(x+3) (x-2). (x+3) (x-2)
<u>2</u><u>x</u><u>^</u><u>2</u><u>-</u><u>4</u><u>x</u><u> </u><u>+</u><u>5</u><u> </u>
<u>(</u>x+3) (x-2)
it's cannot be solved after that.
- 9/ ((-x^2 + 9)^1/2(x+ 3))(x-3)